2004
DOI: 10.1007/s00415-004-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of 201 possible Creutzfeldt-Jakob disease patients

Abstract: Our objective was to describe the clinical signs of 'possible' Creutzfeldt-Jakob disease (CJD) and to investigate whether current diagnostic criteria can accurately differentiate between different forms of dementia. We studied clinical data of 'definite' CJD, Alzheimer's disease (AD), dementia with Lewy bodies (DLB), and vascular dementia (VD) patients. Two subgroups were used: the first consisted of patients with clinical signs compatible with 'possible' CJD but in whom another final diagnosis was made and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
1
21

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 41 publications
9
83
1
21
Order By: Relevance
“…AD was the second most frequent aetiology, followed by DLB. Similar findings have been reported in previous studies [3,4,5,25,26,27]. Vascular encephalopathy was relatively frequent among non-prion RPD, as observed in other postmortem series [4,26].…”
Section: Discussionsupporting
confidence: 91%
“…AD was the second most frequent aetiology, followed by DLB. Similar findings have been reported in previous studies [3,4,5,25,26,27]. Vascular encephalopathy was relatively frequent among non-prion RPD, as observed in other postmortem series [4,26].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have indicated that Alzheimer's disease (AD) is the most frequent alternative diagnosis for CJD [3][4][5][6][7]. Although, generally, there is little difficulty in making a differential diagnosis between CJD and AD, some atypical cases of CJD may present with slowly progressive clinical course mimicking AD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three studies [13][14][15] showed that there were DLB cases diagnosed neuropathologically despite clinical diagnoses as CJD. Haïk et al 13 reported that there were 10 cases (2.2%) of DLB among 465 cases clinically diagnosed as suspected and possible CJD.…”
Section: Discussionmentioning
confidence: 99%
“…Van Everbroeck et al 15 noted that there were 16 cases (8.0%) of DLB among 201 cases clinically diagnosed as possible CJD.…”
Section: Discussionmentioning
confidence: 99%